EP1225 How the conformity of surgical practice with the national guidelines improved the quality of management of ovarian granulosa cell tumors (GCT)? A TMRG and GINECO group study. (1st November 2019) - Lenck, C; Chopin, N; Gouy, S; Bonsang Kitzis, H; Martinez Gomez, C; Radosevic-Robin, N; Martin, S; Lefeuvre-Plesse, C; Lambaudies, E; Leblanc, E; Guyon, F; Classe, J-M; et al.
Abstract : Introduction/Background: Surgery is the cornerstone of ovarian Granulosa Cell Tumor (GCT). Complete resection with adequate staging is the gold standard in 1st line setting. The aim of this study is to assess the impact of an appropriate surgery according to the guidelines. Methodology: This is a nationwide five-year retrospective study, including 463 patients (of the 639 included patients) with a definitive diagnosis of GCT between 2011 and 2016. Medical and surgical practices were analyzed for conformity. Conformity to guidelines was defined by a conservative (unilateral salpingo-oophorectomy) or radical surgery (hysteretomy and bilateral salpingo-oophorectomy) including surgical staging (omentectomy, peritoneal biopsy and peritoneal cytology) according to the FIGO classification. Results: Median age at diagnosis was 49 years old (range 10–89). The median size of tumor was 94 mm (range 5–400). Radical surgery was performed in 240 patients (51, 8%), while a fertility-sparing surgery was performed in 98 cases (21, 2%). A complete surgical staging was performed in only 76 cases (16, 4%). 289 (62.4%) patients received an evaluation of the endometrium (hysterectomy or endometrial curettage). Surgery was fully compliant with the guidelines in 65 patients (14%), partially compliant in 213 patients (46%), non-compliant in 137 patients (29, 6%) and not assessable in 48 cases (10, 4%) respectively. A statistically significant improvement in the surgical management was observed among patients treated after 2012 compared to those treated before 2012. This Improvement included: endometrial evaluation (p=0, 026), tumour rupture rate during surgery (p=0, 010) and the global compliance of the surgery (p<0, 001). Survival data will be reported. Conclusion: Staging surgery provides a better assessment and an appropriate treatment of this rare tumors. According to this study, the implementation of a national network and guidelines dedicated to rare gynaecologic tumors seems to significantly improve the surgical management of the patients with GCT. Disclosure: Nothing to disclose.